PENERAPAN METODE PEMBELAJARAN ROLE PLAYINGDALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS IV SD 166325 KOTATEBING TINGGI - Rismawati Rismawati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This purposes of this research is to improve learning result on Indonesian Languange subject  through role playing method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students fromgrade IV, Elementary School State166325 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the role playing method of Indonesian Languange subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (66,67%), the first cycle (81,81%), cycle II (93,93%)and complete learn the clasical equal to 93,93 %. KeywordS : Role playing, student learning outcomes, Indonesian language